Plasticity in Photoperiodism: Drosophila montana Females Have a Life-Long Ability to Switch From Reproduction to Diapause. Issue 5 (October 2022) - Lankinen, Pekka; Kastally, Chedly; Hoikkala, Anneli
Photoperiodic reproductive diapause is an essential part of female life cycle in several insect species living on high latitudes, where overwintering in reproductive stage involves high risks for survival and progeny production. The sensitive period (SP), during which photoperiodic cues can trigger the switch from direct development to diapause, can last from a few hours or days after emergence to the entire life span of females. Moreover, in some species, sexually mature females can enter post-reproductive diapause as a response to decreasing day length and/or temperature. We studied the duration of SP for diapause induction and the females' ability to enter post-reproductive diapause at short day lengths in Drosophila montana strains from different latitudes in Europe, North America, and Japan. Our study shows that the females of this species have a life-long SP and that they retain an ability to switch between reproduction and diapause as a response to back-and-forth changes in day length for at least 3 months. D. montana strains from different latitudes showed high variation in females' ability to enter post-reproductive diapause; females of the southern strains generally requiring longer time and/or lower temperature to enter this stage than those of the northern strains. Moreover, the proportion of females that switched to post-reproductive diapause in 3 weeks in short day conditions at 16 °C showed positive correlation with the critical day length (CDL) for diapause induction and the latitudinal and continental origin of the strains. Life-long SP increases females' flexibility to respond to short-term changes in environmental conditions and enables reproducing females to switch to post-reproductive diapause when the days get shorter and colder toward the autumn. This ability can play a major role in species phenology and should be taken into account in theoretical and empirical studies on insect adaptation to seasonal variation.